Peranan Perempuan dalam Pengembangan Ekonomi Kreatif - Nenobais, Harry; Unwidjaja, Dwi Satriany; Nugroho, Ferid; Wigrantoro, Mas; Pakpahan, Roy Tumpal; Rahmadi, Muhammad Hanan; Harsono, Budi (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to identify and strengthen the strategic role of women in the development of the creative economy through a community-based participatory empowerment approach. Located in Jagakarsa District, Jakarta, this Community Service activity employed a qualitative descriptive method combined with a participatory approach. Data collection techniques included observation, in-depth interviews, focus group discussions (FGDs), and pre-posttest questionnaires with 35 female micro and small business owners in the culinary and craft sectors. The results showed significant improvements in digital literacy, managerial skills, and product branding skills among participants. Furthermore, the formation of a network of women entrepreneurs strengthened local collaboration and leadership. However, structural barriers such as limited access to financing and the burden of multiple roles hinder business sustainability. These findings confirm that integrating technology-based training, strengthening social networks, and a participatory empowerment approach is an effective strategy for building the capacity of women as key actors in the local creative economy. This research provides a conceptual contribution to gender-based inclusive economic development and a contextual and sustainable empowerment model.